Reducing Readmissions After Stroke With a Structured Nurse Practitioner/Registered Nurse Transitional Stroke Program. Issue 6 (June 2016) - Condon, Christina; Lycan, Sarah; Duncan, Pamela; Bushnell, Cheryl
Abstract : Background and Purpose—: Our aim was to determine whether a standardized Transitional Stroke Clinic (TSC) led by nurse practitioners could reduce 30-day and 90-day readmissions for stroke or transient ischemic attack patients discharged home. Methods—: Phase I consisted of nurse practitioners calling only high-risk patients discharged home within 7 days and performing an office visit within 2 to 4 weeks of discharge. Phase II consisted of all patients discharged home receiving both a 2-day follow-up phone call by a registered nurse and a follow-up visit with a nurse practitioner within 7 to 14 days. Differences in process metrics and readmissions across the 2 phases and overall were assessed. Increasing complexity with multiple chronic conditions (diabetes mellitus, coronary artery disease, and congestive heart failure) was represented in a continuous variable from 0 to 3. Multivariable logistic regression models for 30-day and 90-day readmissions were performed with adjustment for National Institutes of Health Stroke Scale (NIHSS) and previous hospitalizations. Results—: From October 2012 through September 2015, 510 patients were enrolled. From phase I to II, a higher proportion of follow-up calls were made and days from discharge to TSC decreased. Patients readmitted within 30 days were less likely to show for TSC visits (60.85% versus 76.3%; P =0.021). Multivariable modeling showed that TSC visit was associated with a 48% reduction in 30-day readmission (odds ratio, 0.518; 95% confidence interval, 0.272–0.986), whereas multiple chronic conditions and previous stroke/transient ischemic attack increased the risk. TSC visit did not impact 90-day readmissions. Conclusions—: Evaluation in a nurse practitioner–led structured clinic is a model that may reduce readmissions at 30 days for stroke patients discharged home. Abstract : Supplemental Digital Content is available in the text.